BASE NEURAL DE LA ACTIVIDAD ELECTRICA DE LA CORTEZA CEREBRAL - OBRADOR ALCALDE, S (Laboratorio de Estudios Médicos y Biológicos, CD MEXICO, DF, MEX, 1942)
The presence of a substance in serum during normal pregnancy, antagonistic to the hypertensive effect of vasopressin, was tested by injn expts using decapitated cats Individual sera from normal pregnancies had different effects upon the carotid pressur
BOL INST ESTUD MED BIOL
Keywords: BASE, ACTIVIDAD, ELECTRICA, CORTEZA, CEREBRAL; CIENCIAS MEDICAS; MEDICINA INTERNA; NEUROLOGIA